Wybrane pierwiastki szkodliwe w węglu brunatnym ze złoża "Gubin" = Selected toxic elements in lignite from the "Gubin" lignite deposit - Bielowicz, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Gubin" lignite deposit is located in Western Poland, in Lubuskie voivodeship, on the Polish-German border. The study includes analyses results of 20 samples from the Miocene "Gubin" brown coal deposit, taken from 8 boreholes. INAA method has been used to analyze the content of harmful elements, including: As, Zn, Se, Hg, Th, U, while ASA method has been used for Cd and Pb. Studies have shown that the lignite does not contain elevated concentrations of these elements, apart from As, Th and U in some samples, but they are strictly associated with large ash content within this coal.
Keywords: złoże węgla brunatnego "Gubin"; pierwiastki toksyczne; pierwiastki promieniotwórcze; "Gubin" lignite deposit; heavy metals; radioactive elements; harmful elements